THE IMPACT OF AUTHENTIC MATERIALS ON VOCABULARY ACQUISITION IN ENGLISH LANGUAGE LEARNING: A CLASSROOM-BASED STUDY - Juraev Islombek Botirovich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Vocabulary acquisition is considered one of the fundamental components of foreign language learning. In recent decades, researchers and educators have increasingly emphasized the importance of using authentic materials in language instruction as a means of enhancing learners’ linguistic competence and communicative ability. Authentic materials, defined as texts, audio, and visual resources originally created for native speakers rather than language learners, provide exposure to real-life language use and cultural context. This study examines the impact of authentic materials on vocabulary acquisition among students learning English as a foreign language.A mixed-method research design was employed, involving both quantitative and qualitative approaches. The participants consisted of university students enrolled in English language courses. The experimental group was taught using authentic materials integrated into classroom activities, while the control group received instruction through traditional textbook-based methods. Vocabulary tests, classroom observations, and student feedback were used to evaluate the effectiveness of authentic materials.